Risk factors for neonatal death in an inland region in the State of Sao Paulo Brazil - Manzini Sleutjes, Fernanda Cristina; Garcia de Lima Parada, Cristina Maria [UNESP]; Barros Leite Carvalhaes, Maria Antonieta de [UNESP]; Temer, Milena Jamas [UNESP] (Abrasco, 2018)
The main objective of this study was to identify risk factors for neonatal death in an inland region of the State of Sao Paulo. A case-control study was conducted using a case group of 162 child deaths that occurred in 2009 in the states VI Regional Health Department - Bauru. The control group consisted of 324 children selected from the Live Births Information System database who shared the same birth date and city of residence. Univariate and hierarchical multiple logistic regression analyses were performed to identify the factors associated with neonatal death by calculating crude odds ratios adjusted for potential confounders and respective 95% confidence intervals. Results: The likelihood of neonatal death was greater among women who had had a history of infant death (OR = 24.97, CI 12.20 to 51.10) and who had had only up to three antenatal appointments (OR = 11.40, CI = 5, 92 to 21.93), and among infants born at less than 28 weeks of gestation (OR = 168.00, CI = 49.63 to 568.66). The influence of birth weight was also observed among newborns weighing under 1,500g. Conclusions: This study identified five independent risk factors for neonatal death, the most notable of which is maternal history of neonatal death, which has not been properly acknowledged as a risk factor by previous studies.
Keywords: Infant mortality; Epidemiology; Antenatal care; Childbirth